There Has Never Been Anything Truly Wrong with You - Warren, Erin (East Carolina University, 2011)
These stories are about obsessive, lonely people. The characters might seem insane but really, they are just lonely and maybe a bit neurotic. They are introspective characters who began life as sweet children, but grew backbones so that they could appear pitiless, heartless. All that is left then is to privately weep in despair about having become a monster. The writing is often very internal, and the style often tends away from realism. The characters struggle alone through bizarre situations and fears, the purpose of which being that absurdity throws into relief the way our natural emotions are regularly made farcical and embarrassing by a world that wants to deny them or, more often, to ignore them.
Keywords: Literature; Creative; Fiction; Writing; Loneliness--Fiction; Obsessive-compulsive disorder in literature; Introspection in literature